Moyamoya disease with epileptic nystagmus: A case report. (December 2019) - Nakayama, Chie; Mikami, Takeshi; Ukai, Ryo; Chiba, Ryohei; Enatsu, Rei; Suzuki, Hime; Hirano, Toru; Mikuni, Nobuhiro
Highlights: Epileptic nystagmus is extremely rare symptom in moyamoya disease. An ischemic abnormality in the saccade region of the frontal lobe might cause the onset. Revascularization has a possibility to treat the symptoms effectively. Abstract: Epileptic nystagmus is a quick, repetitive, jerky movement of the eyeball caused by seizure activity, which is unaccompanied by other ictal phenomena. We report a case of moyamoya disease with epileptic nystagmus. A 23-year-old woman presented with a headache and transient hemiparesis on her left side. Magnetic resonance imaging showed no ischemic or hemorrhagic stroke lesions. Digital subtraction angiography confirmed stenosis of the terminal portion of the right internal carotid artery and the formation of moyamoya vessels on the right side. 123 I-N-isopropyl-iodoamphetamine ( 123 I-IMP) single photon emission computed tomography (SPECT) showed decreased uptake in the right basal ganglia, frontal, and parietal regions. After electroencephalography (EEG) and a hyperventilation test were performed, nystagmus appeared and was accompanied with a declining level of consciousness. Ictal EEG during an attack showed no epileptiform discharge. Moreover, the patient sometimes experienced simultaneous upper limb-shaking and gelastic attacks. After superficial temporal artery to middle cerebral artery bypass surgery was performed on the right side, symptom frequency and duration gradually decreased. Decreased 123 I-IMP SPECT blood flow in the right frontal region is considered a mechanism that causes the onset of epileptic nystagmus. It is presumed that the attack was caused by an ischemic abnormality in the saccade region of the frontal eye field. Moreover, revascularization can effectively treat the symptoms of moyamoya disease.